Differential expression of inflammasome regulatory transcripts in periodontal disease. Issue 5 (17th October 2019) - Aral, Kübra; Berdeli, Eynar; Cooper, Paul Roy; Milward, Michael Robert; Kapila, Yvonne; Karadede Ünal, Beyza; Aral, Cüneyt Asım; Berdeli, Afig
Abstract: Background: The inflammasome modulates the release of key proinflammatory cytokines associated with periodontal disease pathogenesis. The aim of this study was to evaluate the expression of proteins that regulate the inflammasome, namely pyrin domain‐only proteins (POPs), caspase activation recruitment domain (CARD)‐only proteins, and tripartite motif‐containing (TRIM) proteins, in periodontal diseases. Methods: A total of 68 participants (34 males and 34 females) were divided into four groups, including periodontal health (H), gingivitis (G), chronic periodontitis (CP), and aggressive periodontitis (AgP) based on clinical parameters. Gingival tissue samples were obtained from all participants for reverse transcription polymerase chain reaction (RT‐PCR)‐based gene expression analyses of molecules that regulate the inflammasome, including apoptosis‐associated speck‐like protein (ASC) containing CARD, caspase‐1, interleukin‐1β (IL‐1β), interleukin‐18 (IL‐18), nucleotide‐binding domain, leucine rich family (NLR) pyrin domain containing 3 (NLRP3), NLR family pyrin domain containing 2 (NLRP2), AIM2 (absent in melanoma 2), POP1, POP2, CARD16, CARD18, TRIM16, and TRIM20 by RT‐PCR. Results: NLRP3 and IL‐1β were upregulated in the G, CP, and AgP groups compared with group H ( P < 0.05). AIM2 was downregulated in the CP group compared with the H, G, and AgP groups ( P < 0.05). TRIM20, TRIM16, and CARD18 were downregulated in the G, CP, and AgP groups compared with the H group ( P < 0.05). POP1 and POP2 were downregulated in the CP and AgP, and AgP and G groups, respectively ( P < 0.05). Conclusion: Active periodontal disease may result in downregulation of inflammasome regulators that may increase the activity of NLRP3 and IL‐1β in periodontal disease.